Spatial patterns in intermunicipal Danish commuting - Jorgen Lauridsen; Birgit Nahrstedt (European Regional Science Association (ERSA), 1998)
Intermunicipal variations in in-commuting are mainly explained by variations in number of workplaces, urbanization degree and wealth, whereas variations in out- commuting are mainly determined by variations in workforce size, number of workplaces, living patterns and unemployment. This is quite satisfactory according to existing theory. However, of these explanatory factors only the number of workplaces influences the net in-commuting. But by using spatial lag structures it is shown that unemployment in neighbourhood municipalities influences net in-commuting. Finally, evidence of impact of local spatial industrial patterns on the commuting behaviour is provided, and the nature and reasons for these spatial patterns are discussed.
Keywords: 330